FUTURE CARDIAC EVENTS IN NORMALLY DIAGNOSED GATED MYOCARDIAL PERFUSION SPECT (GSPECT) - H., Amer; K., Niaz; A., Jelani; M., Alqaseer; M., Saleem; M.Y., Sheikh (European Scientific Journal, ESJ, 2015)
Coronary heart disease (CHD) is a major cause of mortality and morbidity in Europe and USA and its management consumes a large proportion of national healthcare budgets. Many studies had tested the prognostic value of a normal myocardial perfusion scintigraphy; they concluded that a normal MPI study is associated with a very low rate of future cardiac events. In view of the above this study is designed to determine the risk of future cardiac events after normal MPS in local population. Methods: This was a retrospective observational registry performed in a single center in the Kingdom of Saudi Arabia. The data were collected from the nuclear medicine database identifying all the reported normal myocardial perfusion scans between January 2008 and December 2011 . Results: There were 290 patients identified with normal cardiac nuclear scans in the pre-specified time frame. Basic patient demographics were outlined and the patients’ charts were reviewed looking for any major cardiac events such as MI or sudden death. Mean follow up was 14.8 months. There were 2 patients that were admitted with NSTEMI and went on to have diagnostic angiograms. One of those two patients underwent percutaneous coronary intervention with stenting. The other patient had nonobstructive CAD and was advised for medical management only. These findings are consistent with a 0.7% risk of cardiac events after a negative scan Conclusion: The above findings demonstrate that the risk of major cardiac events after a negative nuclear cardiac scan is low and is in keeping with the international statistics available.